Teknologi Budidaya Cacing Sutra (Tubifex sp.) di Balai Besar Perikanan Budidaya Air Tawar (BBPBAT) Sukabumi, Jawa Barat - Alni Nuraisyah; Rendi Rendi; Muhammad Abror; Retno Cahya Mukti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Feed is divided into two, namely natural feed and artificial feed. Natural feed is feed given to the larval stage and is the main source of protein for larvae. Silk worms (Tubifex sp.) is one of the natural fish food that contains good nutrition for fish growth. The purpose of this activity is to know the technology of cultivating silk worms (Tubifex sp.) at the Center for Freshwater Aquaculture, Sukabumi, West Java Province. The method used in this activity is field observation and collection of primary and secondary data. The stages of implementing the activities include preparation of containers, manufacture of culture media, stocking of silk worms and maintenance. Parameters observed were silkworm morphology, individual weight, absolute weight growth and specific growth rate and water quality presented in tabular form and processed descriptively. Based on worm rearing data, the specific growth rate was 17.73% day-1 and the weight growth was 249.12 g.